Prevalence of myocarditis in pediatric intensive care unit cases presenting with other system involvement - Hanaa Ibrahim Rady; Hanan Zekri (Elsevier, 2015)
OBJECTIVE: To assess children with myocarditis, the frequency of various presenting symptoms, and the accuracy of different investigations in the diagnosis. METHODS: This was an observational study of 63 patients admitted to PICU with non-cardiac diagnosis. Cardiac enzymes, chest-X ray, echocardiography, and electrocardiogram were performed to diagnose myocarditis among those patients. RESULTS: There were 16 cases of definite myocarditis. The age distribution was non-normal, with median of 5.5 months (3.25-21). Of the 16 patients who were diagnosed with myocarditis, 62.5% were originally diagnosed as having respiratory problems, and there were more females than males. Among the present cases, the accuracy of cardiac enzymes (cardiac troponin T [cTn] and creatine phosphokinase MB [CKMB]) in the diagnosis of myocarditis was only 63.5%, while the accuracy of low fractional shortening and of chest-X ray cardiomegaly was 85.7 and 80.9%; respectively. Cardiac troponin folds 2.02 had positive predictive value of 100%, negative predictive value of 88.7%, specificity of 100%, sensitivity of 62.5%, and accuracy of 90.5%. CONCLUSIONS: Children with myocarditis present with symptoms that can be mistaken for other types of illnesses. When clinical suspicion of myocarditis exists, chest-X ray and echocardiography are sufficient as screening tests. Cardiac troponins confirm the diagnosis in screened cases, with specificity of 100%.